Beyond Mean-Variance: Asymmetric Returns and Downside Risk in an Extreme Frontier Market - Faez Hasan, Mohammed (Iraqi Journal for Administrative Sciences, 2026)
The paper is attempt to understand the asymmetry of the stock return pattern and downside risks on the Iraqi stock exchange, one of the most extreme frontier markets around the world; for the purpose of this study, we have collected and analyzed extensive daily datasets for 57 stocks on the ISX60 index, spanning August 2014 to August 2024, and through the lens of distributional analysis and the lens of various downside risk metrics (i.e., semi-variance, value-at-risk, conditional value-at-risk), and maximum drawdown, such that risk is characterized and analyzed without the usage of standard deviation). What we have discovered is that there is considerable deviation from the normal distribution across the data, where 40.4% of the stocks had a negative skewness, and an overall significant excess kurtosis (mean of 175.13) was present, such that there was no acceptance of normal distribution in our data at any conventional levels of significance. There is a noticeable discrepancy in and of itself by the varying levels of realized downside risk associated with each stock and overall across the collection of the banking sector stocks, i.e., banking sector stocks had a downside risk of an annual return of -14.55% and a maximum drawdown of -82.36% compared to the industrial stocks that have a downside risk of an annual return of +6.41% and a maximum drawdown of -41.24%. There is significant asymmetry evidenced by temporal analysis, as there is a noticeable decline in negative skewness from 61.4% of the stocks during the crisis period (2014-2018) to 26.3% during the stabilization period (2019-2024). In this high volatility environment, the Sortino ratio is a more appropriate measure of risk-adjusted performance than the Sharpe ratio. The results emphasize mean-variance optimization's shortcomings when applied to frontier markets and further reinforce the significance of incorporating measures of downside risk into the construction of portfolios and the management of risk in emerging markets with structural instability and low liquidity.